Double‐Modification Oriented Design of a Deep‐UV Birefringent Crystal Functionalized by [B12O16F4(OH)4] Clusters. (2nd June 2022) - Jin, Congcong; Li, Fuming; Cheng, Bingliang; Qiu, Haotian; Yang, Zhihua; Pan, Shilie; Mutailipu, Miriding
Abstract: Polarization modulation of deep‐UV light is of significance to current technologies, and to this end, the birefringent crystal has emerged as an invaluable material as it allows for effective light modulation. Herein, a double‐modification strategy driven by F and OH anions that makes double effects towards the critical property enhancement of deep‐UV birefringent crystals is proposed. This leads to a new hydroxyborate (NH4 )4 [B12 O16 F4 (OH)4 ] with giant cluster as a deep‐UV birefringent crystal with large birefringence (Δ n exp. =0.12@546.1 nm). This birefringence is a record among inorganic hydroxyborates with experimentally measured birefringence. Structural analysis shows that the near‐plane arrangement of [B12 O16 F4 (OH)4 ] cluster is responsible for the large optical anisotropy. Theoretical calculations indicate that its π‐conjugated [BO3 ] and [BO2 OH] units are the main source of this large optical anisotropy. Abstract : A double‐modification strategy, that is, introducing two types of anions (F and OH), is used to increase the polarizability anisotropy and HOMO–LUMO gap simultaneously. This leads to the discovery a new metal‐free (NH4 )4 [B12 O16 F4 (OH)4 ] with the unprecedented [B12 O16 F4 (OH)4 ] giant cluster as a potential deep‐UV birefringent crystal. It shows the largest birefringence (of Δ n exp. =0.12 at 546.1 nm) among all inorganic hydroxyborates.